Ancient Christian Commentary on Scripture ; OT v.II - Sheridan, Mark; Institute of Classical Christian Studies (Downers Grove, IL IVP, 2002)
Contents : OT v. 2 : Genesis 12-50
Keywords: Bible. O.T. Genesis XII-L -- commentaries; Bible. O.T. Genesis XII-L -- criticism, interpretation, etc. -- history, early church, ca. 30-600 -- sources